The Radicalism Prevention through Academic Policies at State Islamic Higher Education in Indonesia - Nunu Burhanuddin; Khairuddin Khairuddin (Ulumuna, 2022)
Several Islamic higher education institutions have allegedly been exposed to radicalism, which is seen from the emergence of intolerant understanding, extremism, and involvement in terrorism. This study explores the efforts to prevent radicalism by implementing academic policies at State Islamic Higher Education based on experiences at IAIN Bukittinggi, UIN Jakarta, UIN Malang, and IAIN Tulungagung. It employed an ethnographic research method that collected the data through in-depth interviews, extensive observations, and documentation as data collection techniques. The results show that efforts to prevent radicalism were evidenced in the application of general policies of religious moderation in the curriculum and various campus community activities, introduction of campus mottos, tightening of students' selection system, orientation to campus life for new students, strengthening the academic atmosphere, and strengthening students' hard skills, abilities, and soft skills. These show that Islamic higher institutions are actively invloved in the eradication of religious radicalization.